ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA BEAUTIFUL CARD PADA PEMBELAJARAN MATEMATIKA: ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA BEAUTIFUL CARD PADA PEMBELAJARAN MATEMATIKA - Aristiyani, Alfi; Nur Rohmah, Aldila; Hidayati, Yulia Maftuhah; Desstya, Anatri (Universitas Sarjanawiyata Tamansiswa, 2022)
The learning carried out by the teacher is still monotonous, and media needs to be used. This research aims to explore the concept of learning addition and subtraction for applying the beautiful card model and to explore initial information about the media used in learning mathematics to develop beautiful card media. This research is qualitative. This research is only limited to needs analysis. The subjects in the study were first-grade students and teachers in several schools in Tasikmadu District. Field studies carried out the data collection technique by distributing a need questionnaire through a google form to several teachers and first-grade students in Tasikmadu District. The results of this study are: 1) In the first grade of elementary school mathematics, the subject of subtraction and addition still looks abstract; 2) The teacher has not used a media for learning, and the teacher only uses the lecture method. The material provided still feels difficult to understand because it is still abstract, so it requires help to understand a concept using learning media. Keywords: needs analysis; media development; mathematic